Assessing the Usability of UUM's Web Site Through Heuristics - Khor, Puay Puay (2003)
There are several ways in which Web usability can be measured including Heuristic evaluation. Heuristic evaluation is a usability inspection method that requires usability experts to explore the Web site, and identify usability problems by judging whether each element follows established usability principles. The main objective of this study is to identify potential usability problems of UUM’s Web site. Three experts were selected to perform the evaluation. The three experts had evaluated the Web site based on ten heuristics questions given. Each evaluation was observed for one to two hours. Each problem found by the evaluators was classified as a violation of one or more usability principles, or heuristics (based on Jacob Nielsen’s 10 usability heuristics). From the analysis of the severity ratings, there are two major usability violations/problems faced by users when browsing UUM’s Web site. The first major problem relates to the design of the Web site which is not flexible for efficient use (Heuristic No. 7). Second, there is insufficient information/help for users to recognise, diagnose, and recover from errors (Heuristic No. 9). Eleven usability problems were identified and discussed in this report together with twelve recommendations to solve the major problems.